The dynamics of insurance demand under liquidity constraints and insurer default risk - Liu, Yanyan; Myers, Robert J. (International Food Policy Research Institute, 2012)
Low demand for micro-insurance has been a prominent problem in developing countries. We study the dynamics of insurance demand by risk-averse farmers who can borrow and lend subject to a credit constraint and who also perceive a risk of insurer default. Credit constraints and the possibility of insurer default both reduce the demand for insurance. We then propose an alternative insurance design that allows farmers to enter an insurance contract while delaying payment of the premium until the end of the insured period. We show how this alternative design can increase insurance take-up by relaxing the liquidity constraint and assuaging farmers’ concerns about insurer default. We also investigate the effects of the associated problem of farmers reneging on their delayed premium payment if the insured event does not occur.